PENGEMBANGAN MEDIA CERITA BERSERI BERBASIS POP-UP BOOK UNTUK PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA ARAB KELAS X MA DI KABUPATEN NGANJUK - Putri Ayu Oktavia; Nafis Azmi Amrullah; Darul Qutni (Universitas Negeri Semarang, 2023)
This research was launched by the problem of X-class MA students in Nganjuk district who find it difficult to understand learning Arabic-speaking skills. The difficulties of students are caused by several factors such as previous school backgrounds, the absence of learning media capable of arousing students' interest in learning, and the lack of intensity in the use of Arabic in everyday life. For this reason, researchers are trying to develop a learning medium for speaking skills that is a pop-up book-based storyline. This research is part of the type of research and development using 4D procedures aimed at delivering new innovations as well as solutions to the problem of learning Arabic-speaking skills. The data collection techniques used in this study are interviews, lifts, observations, and documentation. The results of this study show that teachers and students strongly agree with the idea of developing a pop-up book-based storytelling media for learning Arabic-speaking skills. Media products in this research have already gone through the validation phase of linguists and materials, media designers, and validation by practitioners/teachers. As for the results of validation by the linguist and material obtained a score of 4.61 which belongs to the 5 scale, the validation of the media designer obtains a scale of 4.31 which is included in the 5 Scale. From the two validation scores already obtained, it can be concluded that the whole aspect studied on Pop-Up Book-based Storytelling Media is worthy of use or development. In addition, there are test results of a Pop-Up Book-based Stories Series Media product using a student's qualifying response lift. The media responsiveness elevator obtains a 79% percentage that falls on scale 4. It means that the student fully agrees with the aspects studied in Pop-Up Book-based Storytelling Media, whether it is the material aspect, the appearance, and also the function of the media when used in learning activities.